General regularities of seismic activity of Northern Armenia in connection with block structure and tectonic activity - K. S. Ghazaryan; R. S. Sargsyan (Геодинамика и тектонофизика, 2020)
The study is focused on searching for spatial regularities in the occurrence of earthquake hypocenters in different geological settings in Northern Armenia. Tectonic-geomorphological indices are applied to define the tectonic activity of blocks composing the study area, which was manifested within a long period of time, starting from the neotectonic development period. The blocks are classified accordingly. The regional seismic activity is analysed considering the block structure of the study area. Earthquake focal mechanisms are determined, and dominant displacement trends are identified. Based on the comparative analysis of the blocks’ tectonic activity indicators and the locations of seismic events differing in strength, regular patterns of spatial distribution of seismic events are identified. It is established that the earthquake hypocenters of different strength occur in certain block structures; and the predominant types of movements in the earthquake hypocenters are largely determined by types of fault structures. It is emphasized that investigating the blocks’ neotectonic activity is important for discovering the general patterns of spatial distribution of seismic events.